Examples

Example 1 (i)

Example 1 (ii)

Example 1 (iii) Important

Example 2 (i)

Example 2 (ii)

Example 2 (iii)

Example 3 Important

Example 4

Example 5 Important

Example 6

Example 7 Important

Example 8 Deleted for CBSE Board 2022 Exams

Example 9 Important Deleted for CBSE Board 2022 Exams

Example 10

Example 11 Important

Example 12 Important

Example 13 Important You are here

Example 14

Example 15 Important

Example 16 (i)

Example 16 (ii)

Example 17

Example 18 (i) Important

Example 18 (ii)

Example 19

Example 20

Example 21 Important

Example 22 (i)

Example 22 (ii)

Example 23 (i) Important

Example 23 (ii)

Example 24 Important

Example 25 Important Deleted for CBSE Board 2022 Exams

Last updated at Aug. 25, 2021 by Teachoo

Example 13 (Splitting the middle term) Factorise 6x2 + 17x + 5 by splitting the middle term, and by using the Factor Theorem. 6x2 + 17x + 5 We factorize using the splitting the middle term method = 6x2 + 2x + 15x + 5 = 2x(3x + 1) + 5(3x + 1) = (3x + 1) (2x + 5) Example 13 (Factor Theorem) Factorise 6x2 + 17x + 5 by splitting the middle term, and by using the Factor Theorem. Step 1: We check if x2 is multiplied by 1. 6x2 + 17x + 5 = 6 ("x2 + " 17/6 " x + " 5/6) = 6 p(x) Step 2: We factorize p(x) Let "x2 + " 17/6 " x + " 5/6 = (x – a) (x – b) So, ab = Constant term = 5/6 We find factors of 5/6 5/6 = 5/6 × 1 5/6 = 5/3 × 1/2 5/6 = 5/2 × 1/3 So, factors of 5/6 are 1, 5/3 , 5/2, 1/3 , 1/2 We take value of x as 1, 5/3 , 5/2, 1/3 , 1/2 –1, (−5)/3 , (−5)/2, (−1)/3 , (−1)/2 and check value of p(x) i.e. "x2 + " 17/6 " x + " 5/6 Hence, a = (−5)/2 , b = (−1)/3 Now, "x2 + " 17/6 " x + " 5/6 = (x – a) (x – b) = ("x – " ((−5)/2))("x – " ((−1)/3)) = ("x + " 5/2) ("x + " 1/3) So, 6x2 + 17x + 5 = 6 ("x2 + " 17/6 " x + " 5/6) = 6 ("x + " 5/2) ("x + " 1/3) = 6 ((2𝑥 + 5)/2) ((3𝑥 + 1)/3) = (2𝑥 + 5) (3𝑥 + 1)